1991
DOI: 10.1111/j.1399-0039.1991.tb02021.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA association of idiopathic Peyronie's disease: An indication of autoimmune phenomena in etiopathogenesis?

Abstract: HLA typing for class I and class II antigens was done in 52 unrelated patients suffering from idiopathic Peyronie's disease. The controversially discussed association with the HLA-B7 cross-reacting group could not be confirmed. Marked deviations of antigen frequencies were observed for HLA-A1, B8, Cw7, DR3 and DQw2 compared to healthy local controls. After correction of p-values, A1 (pc less than 0.05) and DQw2 (pc less than 0.01) remained significant. A possible association of Peyronie's disease with markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 13 publications
0
16
0
4
Order By: Relevance
“…They found a positive correlation only with HLA B27 and concluded that, because none of the bacterial cultures were positive, molecular mimicry or infection was not responsible for PD. 27 Rompel et al 12,13 performed HLA typing on 52 unrelated individuals with PD using a modi®ed lymphotoxicity test for both class I and II MHC. They found a statistically signi®cant association with HLA A1 and HLA DQw2, and in their 1994 study, they reported an association with HLA B8, Cw7 and DR3.…”
Section: Discussionmentioning
confidence: 99%
“…They found a positive correlation only with HLA B27 and concluded that, because none of the bacterial cultures were positive, molecular mimicry or infection was not responsible for PD. 27 Rompel et al 12,13 performed HLA typing on 52 unrelated individuals with PD using a modi®ed lymphotoxicity test for both class I and II MHC. They found a statistically signi®cant association with HLA A1 and HLA DQw2, and in their 1994 study, they reported an association with HLA B8, Cw7 and DR3.…”
Section: Discussionmentioning
confidence: 99%
“…This haplotype has been associated with numerous autoimmune disorders and is also increased in insulindependent diabetes. It has therefore been suggested that Peyronie's disease may be due to an autoimmune disorder and may also have an inherited predisposition similar to other autoimmune diseases [13,14]. Nyberg et al [16] reported father-to-son transmission of Peyronie's disease and Dupuytren's contracture in three generations and suggested that this was an autosomal dominant trait.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors concluded that the prevalence of diabetes mellitus tended to be higher in Peyronie's disease patients than in the control population, but the difference was not statistically significant [8]. Other authors attempted to find an immunogenetic basis for Peyronie's disease and revealed the coincidence of autoimmune disorders in Peyronie's disease [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Существует несколько теорий развития данного заболевания. Возникновение болезни Пейрони связывали с недо-статком витамина Е, приемом β-блокаторов [7, 8], повышением уровня серотонина [9], гормональ-ной инволюцией [10], генетической предрасполо-женностью и связью с контрактурой Дюпюитрена и HLA-B7 перекрестнореактивной группой анти-генов [11, 12, 13]. Но наибольшее распространение получила посттравматическая теория.…”
Section: этиология и патогенезunclassified